Tourism innovation in the digital era : big data, AI and technological transformation - Valeri, Marco (New perspectives in tourism and hospitality management, 2023)
Digitalization and artificial intelligence are increasingly influencing modes of travel planning, exploration of new destinations, and promotion of them. The potential of new technologies to completely overhaul the tourism and hospitality industry is emerging; new generations of tourists will have radically different expectations and requirements in relation to today's tourists. The sharing economy and the experience economy strongly influence the creation of new business models in tourism. Many low-income economies can potentially benefit from this digital transformation and others are at risk of being left behind if they fail to embrace this moment. To explore how and why, ten chapters are presented here in Tourism Innovation in the Digital Era, ranging from topics as diverse as big data analytics in tourism marketing to the impact of AI to the use of CSR in competitiveness amongst hotel groups. Providing multidisciplinary approaches, readers will learn more about the organizational impacts of digitalization and artificial intelligence in tourism and hospitality. The book series New Perspectives in Tourism and Hospitality Management positions organizational change and behavior in the tourism and hospitality sector at its heart, providing interdisciplinary research in this field and joining the areas of organizational studies and tourism/hospitality management.